A non-linear complex diffusion based fi lter adapted to Rayleigh's speckle noise for de-speckling ultrasound images - Srivastava S.; Srivastava R.; Sharma N.; Singh S.K.; Sharma S. (My University, 2025)
In this paper, an edge and structure preserving non-linear complex diffusion based fi lter adapted to Rayleigh's speckle noise for speckle reduction from 2D ultrasound images is proposed and implemented in MATLAB 7.0. The initial condition of the proposed fi lter is the speckle noised ultrasound image and the speckle-reduced image is obtained after certain iterations of the fi lter till its convergence. For digital implementations, the proposed scheme has been discretised using the fi nite difference scheme. The performance of the proposed complex diffusion-based fi lter has been evaluated both qualitatively and quantitatively. A comparative study of the proposed scheme with other standard speckle reduction schemes such as the homomorphic Wiener fi lter, the Lee fi lter, the Frost fi lter, the Kuan fi lter and the Speckle Reducing Anisotropic Diffusion (SRAD) fi lter for several ultrasound images with varying amounts of speckle noise variance is also presented. The obtained results show that the proposed non-linear complex diffusion-based scheme performs better than all other schemes in consideration and is also well capable of preserving edges and fi ne structures from ultrasound images during speckle reduction. Copyright © 2012 Inderscience Enterprises Ltd.